Dental implant status in elderly individuals requiring domiciliary dental care in Japan - Yoshiyuki Hagiwara; Tetsuo Ohyama; Hiroyasu Yasuda; Keisuke Seki; Takayuki Ikeda (SpringerOpen, 2021)
Abstract Background The presence of implants is a significant burden not only for dentists but also for caregivers and families of elderly individuals requiring nursing and domiciliary dental care. However, few reports have assessed the status of domiciliary dental care or measures employed to deal with related issues. Hence, we aimed to evaluate the dental implant status in elderly patients requiring nursing and domiciliary dental care and to determine the suitable measures for overcoming the associated limitations. A questionnaire was mailed to 1000 dentists who provided domiciliary dental care in the Tokyo metropolitan area of Japan. The questions were classified into three categories: basic information of the dentists, actual implant status of patients requiring domiciliary dental care, and implants in an aging society. Results The response rate was 36.5%. Approximately 2% of patients requiring domiciliary dental care were implant patients. Many implant-related problems were associated with insufficiency or difficulty in cleaning around the implant, resulting in peri-implantitis. Prosthetic and more serious complications such as implant body fracture or loss were reported and frequently managed by routine follow-ups, cleaning the area around the implant, scaling and polishing, and/or pharmacological modalities. Oral care mainly involved simple toothbrushing instructions, which was not adequate. Conclusions Our findings suggest the necessity of simplifying the oral environment and making oral care a simple task before aging individuals require nursing and domiciliary dental care.